2000
DOI: 10.1021/ma990614s
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Dewetting in Nanoparticle-Filled Polymer Films

Abstract: The perturbing influence of nanosize filler particles on the dewetting of spun-cast polymer films is investigated. Previous studies have shown that spun-cast films of unentangled polystyrene (PS) and polybutadiene (PB) dewet acid-cleaned silicon wafers when the films are annealed above their bulk glass transition temperature T g. It is also known that "impurity" particles tend to promote dewetting in thin polymer films. Here we demonstrate that the addition of a small amount of C60 fullerene nanoparticles to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
230
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 181 publications
(242 citation statements)
references
References 26 publications
12
230
0
Order By: Relevance
“…While there has been no result reported on the formation of ultrathin liquid films that are stable, there have been several studies reported for the stability of thin polymer films, involving the use of grafting [20][21][22] and nanoparticles. 23 However, the film thickness is on the order of 100 nm, whereas the thickness of the stable film in this study is on the order of 1 nm.…”
Section: ͑4͒mentioning
confidence: 54%
“…While there has been no result reported on the formation of ultrathin liquid films that are stable, there have been several studies reported for the stability of thin polymer films, involving the use of grafting [20][21][22] and nanoparticles. 23 However, the film thickness is on the order of 100 nm, whereas the thickness of the stable film in this study is on the order of 1 nm.…”
Section: ͑4͒mentioning
confidence: 54%
“…Here, we show that the addition of fullerenes [15] (C 60 ) to both PECH and BSP3 inhibits dewetting of thin polymer films. In Figure 3 In Figure 3-3, fullerenes were added to the same solution of PECH as above and then spin-coated.…”
Section: Resultsmentioning
confidence: 76%
“…As a sample calculation, consider a chain with N = 20 sites of diameter σ = 6.65 Å (using N = M/m o , this corresponds to PS with molecular weight 2040, a fairly short chain but about the same length as those used by Barnes et al [20]), and nanoparticles with diameter 1.5 σ ≈ 10 Å, i.e. 1 nm.…”
Section: Equation 3-1mentioning
confidence: 99%
“…The syntheses of nanometersized components have extended beyond carbon [2,10,[16][17][18][19][20]. A drawback to the utilization of carbon nanotubes, based on conductivity, is the inability to control the chirality.…”
Section: Resultsmentioning
confidence: 99%
“…Poly(2-methoxy-5-ethylhexyloxy-1,4-phenylene vinylene) (MEH-PPV)/rutile-TiO 2 composite films were made by Kim [19] with various sizes from 7 to 23 nm and their electroluminescent characteristics were investigated. Barnes [20] investigated the perturbing influence of nanosize filler particles on the dewetting of spun-cast polymer films. Rotkin [21] developed a new heuristic model for the calculation of the formation energy of the carbon nanoclusters.…”
Section: Resultsmentioning
confidence: 99%